EPCO-02. GENOME-WIDE DNA METHYLATION PROFILING AND GENETIC CHARACTERIZATION OF LONG-TERM SURVIVAL IDH WILD-TYPE GLIOBLASTOMA PATIENTS. (14th November 2022) - Miele, Evelina; Lazzarini, Elisabetta; Ciolfi, Andrea; Pedace, Lucia; Nardini, Claudia; Patrizi, Sara; Mastronuzzi, Angela; Tartaglia, Marco; Anghileri, Elena; Calatozzolo, Chiara; Lamperti, Elena Antonia; Patanè, Monica; et al.
Abstract: Glioblastoma multiforme (GBM) has a dismal outcome of approximately 12 months. Less than 5% of patients (long-term survivors-LTS) survives more than 5-years, including IDH-mutant gliomas. Nevertheless, the molecular fingerprint of LTS remains largely uncharted. DNA methylation (DNAm) is an epigenetic modification, altered in cancer and used to classify brain tumors. In this multicentric study sponsored by Alleanza Contro il Cancro (ACC) network, we aimed to molecularly characterize LTS vs standard survival GBM (CTR) by DNAm/Copy Number Variation (CNV) and mutation profiling. We analyzed 51 IDHwt GBM samples (27LTS/24CTR) by Illumina EPIC beadChip and AmpliSeq Comprehensive Cancer Panel. We ran methylation data through the brain tumor classifiers v11b4 and v12.5, performed multidimensional scaling analysis and investigated differentially methylated regions (DMR) correlating them with survival. According to v11b4, cases were classified as: 43 GBM IDHwt (22LTS/21CTR), 27 with a calibrated score >0.84 (16LTS); Plexus Tumor with low scores (2LTS/3CTR); 3 LTS samples did not match. A diagnostic refinement was observed by the v12.5, with 48 cases classifying as GBM IDHwt (25LTS/23CTR) and 35 (19LTS) with optimal score. The LTS group was more heterogeneous, with 4 cases matching in the pedHGG subtypes, including 2 cases in young adults, one with high tumor mutational burden and MSH6 mutation. No specific DNAm genomic profile was observed for LTS patients but we identified 18 significant DMRs, 4 associated with survival probability. At CNV analysis, most cases showed classical alterations (Chr7 gain with or w/o EGFR amplification, 9p21 loss, Chr10 loss) while pedHGG were associated with PDGFRA amplification, 1q gain, 13q loss. NGS identified at least 1 pathogenic variant in 40 cases (22CTR/18LTS) and showed a higher prevalence of mutation negative cases among LTS. No significant difference between the 2 groups was observed in terms of prevalence of mutated genes or number of VUS per sample.